Capacity improvement through adaptive power control in CDMA system - Kiong T.S.; Eng K.S.S.; Ismail M. (Institute of Electrical and Electronics Engineers Inc., 2023)
In event of global wireless communication system becoming more advance, the introduction of code division multiple access (CDMA) pioneered by QualComm, Inc., of San Diego is both timely and favorable. The CDMA interface standard studied in this project is the IS-95 standard. The major attributes of CDMA IS-95 are high system capacity, cost effectiveness and increment in quality of service. The point of interest of this study is capacity improvement through adaptive power control. Three different power control schemes are studied in this research. Eb/No (energy per bit to noise density) is used to measure the reverse link signal quality. The lower the Eb/No, the higher is the capacity. However, there need to be a compromise between Eb/No and capacity as decreasing the Eb/No below a certain limit jeopardizes the link quality. 2003 IEEE.